Penerapan Metode Total Opportunity Cost Matrix-Sum Approach (TOCM-SUM APPROACH) dalam Mengoptimalkan Biaya Transportasi (Studi Kasus: PT. Ciomas Adisatwa Padang) - Melisa Melisa; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2021)
Product distribution issues are common to happen in a business company. From many factors in a company to maximize profits, one of them is the ability to deliver products on time at the minimum cost in transportation. PT. Ciomas Adisatwa Padang distributes their products in the area of the depot and spends a lot of money. If the transportation costs are too much the company will earn small profits. Transportation method to solve problems that involve minimizing transportation costs or product delivery from source to destination is Total Opportunity Cost Matrix-Sum as initial feasible solution and Stepping Stone as an optimization test that is useful for determining the results of optimizing transportation costs and the number of product shipments from each warehouse to destination. The result is carried out using secondary data recorded from the PT. Ciomas Adisatwa Padang in July 2021 in applied research. The initial method of Total Opportunity Cost Matrix-Sum Approach gave Rp. 8.677.366, which was then followed by the Stepping Stone method, which gave Rp. 8.030 974. As a result, the company can save 21% of the total cost on transportation costs in advance.